FORMATION OF LONG-TERM MODEL OF RESTRUCTURING OF HOSPITAL BEDS FOR UROLOGY PROFILE - V. M. Ivanov; Ju. A. Anosova; O. V. Zolotukhin; M. V. Kochetov; Yu. Yu. Madykin (Исследования и практика в медицине, 2015)
Abstract:One of the leading causes of reduced quality of life, disability and premature mortality were urologic diseases. Improving the provision of urologic care to the population — one of the major problems in the system. The team of authors developed a model of restructuring urological service to the region with a total population of 2 million people, and a regional center with a population of 1 000 thousand people. The article provides the calculation of normative number of beds and doctors’ rates for the urology department three-tier system of care, depending on the population of the region. The calculation of staffing urologist and urological department heads. Computer simulation is performed in accordance with the current legislation (about health care) and regulations. The standardized software development methodology inter-networking model units have practical value and can be used by the executive bodies of state power in the health sector of any region of each profile of care.